Řízení vztahů se zákazníky - Berka, Aleš (Univerzita Pardubice, 2006)
The paper provides a view on the concept of CRM (Customer Relationship Management) and stresses out the importance of information feedback and readiness for implementation of CRM. The author deals with principles of customer relationship management and customer satisfaction survey. This article also focuses on impacts of implementation of CRM and principles of loyalty programmes.
Keywords: vztahy se zákazníky; Management; loajalita zákazníka; zákaznický servis; Implementace